Understanding the psychological pathways to translation technology competence: emotional intelligence, self-esteem, and innovation capability among EFL students - Junfeng Zhao; Xiang Li; Jin Wei; Xinyuan Long; Zhaoyang Gao (BMC Psychology)
Abstract Background The accelerated advancement of information technology and artificial intelligence in the modern globalized world has necessitated a high level of technology competence from translators to adapt to the increasing needs of clients and the language industry. Prior research indicated that emotional intelligence, self-esteem, and innovation capability independently affected students’ translation competence. However, no research has investigated how these psychological factors influence student translators’ proficiency in translation technology. Methods This research engaged 663 senior EFL students through an online questionnaire to investigate the systematic associations among the identified variables. Descriptive statistics, structural equation modeling, and the bootstrap method were adopted to analyze the collected data. Results The results showed that students’ translation technology competence (TTC) was significantly influenced by emotional intelligence, self-esteem, and innovation capability. Furthermore, self-esteem and innovation capability were independent and sequential mediators in the connection between emotional intelligence and TTC of college EFL students. Conclusions This study provides theoretical and practical insights for designing curricula and interventions to enhance TTC by integrating psychological and pedagogical strategies. By emphasizing emotional intelligence, fostering self-esteem, and cultivating innovation capability, educators and institutions can prepare students to meet the demands of the technology-driven language service market.